The effect of clove oil on frozen storage stability and quality of rainbow trout (Oncorhynchus mykiss) - Coban, Ozlem Emir; Ozpolat, Emine; Kuzgun, Nermin Karaton (Ege Univ, Fac Fisheries, 2018)
The present study evaluated clove oil (0.5% and 1% v/w) use as a natural preservative on the quality of frozen rainbow trout fillets during of six months. Vacuum packed samples were stored at -18 degrees C. Microbiological parameters (total anaerobe, psychrophilic bacteria, lactic acid bacteria, mold-yeast) and sensory quality (odour, color and texture) were determined during the storage period. Microbial growth was high over a period of frozen storage for control samples. The existence of clove oil demonstrated to develop the sensory quality of frozen rainbow trout fillets when used in combination with vacuum pack. According to our results, clove oil as natural protective and influential antibacterial can be used in conjunction with vacuum pack to augment frozen stored rainbow trout quality.
Keywords: Essential oil; clove oil; rainbow trout; frozen storage; microbiological quality; sensory quality